Formative Assessment —Theory Vs Practice An Experience from Higher Secondary Schools of Kerala - K, Vijayan.; Patidar, Jitendra Kumar (JOURNAL OF INDIAN EDUCATION, 2013)
Formative Assessment is an on going evaluation of student performance for the purpose of assessing student learning and planning instruction. Many state boards and national boards like CBSE already implemented Formative Assessment as a component of Continuous and Comprehensive Evaluation (CCE). In Kerala it has been implemented since 1997 at various levels of school education. The present study aims to find out how far the formative assessment practices in the higher secondary classroom correlated with the summative assessment scores over the years. Documentation analysis was used for collecting relevant data for the study. Higher Secondary Board Examination results of 100 students under Science stream from two schools were collected during the year 2007 and 2010 respectively from the school records. The data were analysed with the help of correlation and t-test. The study reveals that correlation between formative assessment and summative assessment was positive in all subjects but small and negligible. More over it was found that there exist no difference in the correlation between formative assessment and summative assessment during 2007 and 2010.